The Distance Monitoring of Blood Pressure as a Tool for Improving of the Quality of Follow-Up Observation of Patients with Arterial Hypertension - I. A. Starodubtseva; Yu. A. Sharapova (Архивъ внутренней медицины, 2021)
This article focuses on the distant blood pressure monitoring for patients with arterial hypertension. As numerous studies show, even slightly elevated blood pressure significantly raises the risk of cardiovascular complications. And, vice versa, a 5 mmHg decrease in blood pressure reduces the lethality risk. Therefore, it is not enough to prescribe the right medication but also it is of paramount importance to monitor patients’ compliance with the treatment. Clinical observation of patients with arterial hypertension is an effective tool for the prevention of cardiovascular complications. However, to date, the coverage of follow-up and the achievement of blood pressure targets in patients with arterial hypertension is one of the most problematic aspects. Distance monitoring of blood pressure opens more opportunities for the doctor’s involvement, timely assessment and adjustment of the medication. The results of domestic and foreign research show high efficacy of the distance blood pressure monitoring. Positive results regarding the achievement of target blood pressure after 3 months are shown when using the technology of blood pressure monitoring and distance counseling of patients with arterial hypertension. In particular, the article considers the technology of mobile health care (mHealth), which is a more flexible platform for a patient’s continuous self-care.